IMPLEMENTATION OF TEACHING FACTORY IN GRADE XI BUSINESS ENGINEERING AND MOTORCYCLES AT STATE VOCATIONAL SCHOOL 1 KUALA KURUN - Domok, Kasino; Sri Murwantini; Muhammad Hudan Rahmat (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
This research aims to evaluate the effectiveness of the Teaching Factory (TEFA) model implementation at SMK Negeri 1 Kuala Kurun, specifically in the Business Engineering and Motorcycle (TBSM) program. Using a sequential explanatory design research method, the analysis reveals the complexities involved in implementing TEFA, which encompasses various factors influencing the success and suboptimality of the program. Data collected through questionnaires and interviews reveal a significant gap between the established targets and the achieved outcomes, with the highest gap value found in the variable of TEFA's alignment with student expectations. This indicates an opportunity to improve the alignment between program implementation and student expectations. Additionally, factors such as teacher readiness and infrastructure also play a role, although the gaps in these areas are relatively smaller. The variables related to learning and practice, while contributing the least, remain important as teacher support and opportunities to apply theory significantly influence students. Recommendations from this study include a comprehensive evaluation of the curriculum, improvement of facilities, and better management of time and Quality Control (QC) systems, aimed at enhancing the effectiveness of TEFA. This research emphasizes the need for integration between the curriculum and industry demands to prepare students for the challenges in the workforce